Nano-colloids of Sn2P2S6 in Nematic Liquid Crystal Pentyl-cianobiphenile - Kurochkin, O.; Atkuri, H.; Buchnev, O.; Glushchenko, A.; Grabar, O.; Karapinar, R.; Reshetnyak, V.; West, J.; Reznikov, Yu. (Condensed Matter Physics, 2010)
It has been shown experimentally that the ferroelectric nano-particles, in common with other molecular additives, shift the clearing temperature, Tc, extending or reducing the two-phase coexistent region and changing the average order parameter of the single-component nematics. An increase of up to 11°C or a smaller decrease of as much as 3°C of Tc, and corresponding changes of the order parameter were observed. In all cases the order parameter of the colloid followed the universal temperature behaviour, which is a characteristic of LCs with molecular additives.